Verification of ACI- 549 Code for Flexural Strengthening of Reinforced Concrete Beams Using FRCM - Afzal, Muhammad Shekaib; Ebead, Usama (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This paper presents an analytical study to verify the ACI 549-4R-16 code for experimentally tested Reinforced Concrete (RC) beams, which were strengthened to enhance the flexural capacity using Fiber-Reinforced Cementitious Mortars (FRCM). Twelve RC beam specimens having 2500 mm length, 150 mm width, and 260 mm depth were prepared with two different reinforcement ratios (?_s^D12=0.72% and ?_ s^D16=1.27%), and were then strengthened with two different FRCM systems, namely carbon and polyparaphenylene-benzobisoxazole (PBO) FRCM systems. Two RC beams were tested as control specimens. Six beams were externally reinforced using single, double and triple layers of carbon FRCM system, while the remaining four beams were repaired with one and two layers of PBO FRCM system. The strengthened RC beams were tested in flexural under four-point monotonic loading. The experimental results revealed that a reasonable gain in flexural strength was achieved for both FRCM systems, with up to 78% increase in flexural capacity for carbon FRCM systems and up to 27.5% for PBO FRCM system over that of their control specimens. Further, the results obtained from the theoretical approach using the ACI 549 code conform well with the experimental loadcarrying capacities. Moreover, the values obtained for experimental to theoretical ratio are quite close to 1.00 which somewhat shows satisfactory computational results.